Assessments in occupational therapy mental health : an integrative approach - Hemphill, Barbara J., ....-; Urish, Christine K., ....- (Thorofare (N.J.) : Slack, 2020)
Assessments in Occupational Therapy Mental Health: An Integrative Approach, Fourth Edition is a unique compilation of mental health assessments that are taught in occupational therapy academic programs and used in clinical practice. This highly anticipated Fourth Edition provides the occupational therapy student and educator with knowledge about the evaluation process, assessments that are current and accurate, and how to generate research for developing assessment tools.
Keywords: Ergotherapie; Mentale gezondheid